Mobile Phones, Social Capital, and Internal Migration in Indonesia - Yanti, Mery; Yusnaini, Yusnaini; Alamsyah, Alamsyah (Populasi, 2025)
This study investigates internal migration in Indonesia using logistic regression to analyze the impact of nine independent variables: social participation, social capital, risk-taking attitudes, age, marital status, gender, education level, mobile phone ownership, and internet access. The data were derived from the 5th Indonesian Family Life Survey (IFLS), which included 16,204 households and 50,418 individuals across 13 provinces. Respondents comprised of households’ head, their partners, and family members aged 15 years and older. The findings indicate that education level, internet access, marital status, and social capital significantly influence internal migration. Specifically, the contributions of these variables to explaining internal migration were 58.36% (OR: 1.401) for education level, 58.17% (OR: 1.398) for internet access, 51.63 % (OR: 1.068) for social capital, and 49.7% (OR: 0,987) for marital status, cumulatively explaining 1,55% of the variance in migration outcomes, with a Chi-square (X2) of 153,16 and p < 0.000. Based on these results, it is recommended that the government develop new economic growth centers, enhance social capital at the community level, and improve the information and communication technology infrastructure nationwide to optimize the benefits of internal migration for societal welfare.